PENGARUH PENERAPAN KURIKULUM MERDEKA DAN MOTIVASI BELAJAR SISWA TERHADAP PEMAHAMAN MATEMATIS PADA MATERI ALJABAR - Rakhmawati Muhammad, Rosida; Ayulia, Desi; Desta Ranti , Ingga; Miftahul Jannah , Reza (Jurnal Lebesgue : Jurnal Ilmiah Pendidikan Matematika, Matematika dan Statistika, 2024)
The purpose of this study is to analyze the influence of the merdeka curriculum and student motivation on student understanding and the relationship between curriculum and motivation on student understanding in learning mathematics on algebra material by focusing on observations of the learning process carried out by teachers. The data analysis technique used multiple regression tests and data collection using post tests and questionnaires. The subjects in this study were 8th grade students of SMPN 36  Bandar Lampung in the 2024/2025 academic year with a sample size of 54 people. The results of this research indicate that the implementation of the merdeka curriculum and student learning motivation do not have a significant influence on students' mathematical understanding of algebra material.